2020
DOI: 10.1369/0022155420911049
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Expression of Interleukin-33 and ST2 in the Mouse Reproductive Tract Is Influenced by Superovulation

Abstract: Interleukin-33 (IL-33) is an IL-1 family cytokine with pleiotropic effects on diverse cell types. Dysregulated IL-33 signaling has been implicated in pregnancy-related disorders, including preeclampsia and recurrent pregnancy loss, and in ovarian function in women undergoing controlled ovarian stimulation for in vitro fertilization. To date, expression of IL-33 and its receptor subunit, ST2, in the female reproductive tract remains poorly characterized. We identify IL-33-expressing oocytes surrounded by ST2-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
3
2
Order By: Relevance
“…However, whether and how IL-33 supports events that precede implantation are less clear. While we find that total implantation site numbers at E7.5 are reduced in IL-33 KO dams, the modest nature of this reduction suggests that IL-33 may play relatively minor roles in the reproductive processes that are required to initiate implantation in mice—such as oogenesis and oocyte release during estrus, oocyte fertilization, and blastocyst attachment—notwithstanding our prior finding that IL-33 is expressed in the ovaries and uteri of virgin mice and through E2.5 in pregnancy ( 50 ).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…However, whether and how IL-33 supports events that precede implantation are less clear. While we find that total implantation site numbers at E7.5 are reduced in IL-33 KO dams, the modest nature of this reduction suggests that IL-33 may play relatively minor roles in the reproductive processes that are required to initiate implantation in mice—such as oogenesis and oocyte release during estrus, oocyte fertilization, and blastocyst attachment—notwithstanding our prior finding that IL-33 is expressed in the ovaries and uteri of virgin mice and through E2.5 in pregnancy ( 50 ).…”
Section: Discussioncontrasting
confidence: 59%
“…The relative, stage-specific requirements for IL-33 in early pregnancy progression may reflect differences in the uterine cell types that express IL-33 in the pre- versus post-implantation stages of early pregnancy. For example, we have previously shown that glandular and luminal epithelial cells are the main IL-33 + cells in the endometrium at E2.5 ( 50 ), whereas we now show that stromal cells and endothelial cells are the main IL-33 + cell types in the decidua during the post-implantation stage of early pregnancy, although IL-33 expression by decidual endothelial cells during this time frame is transient and peaks at E7.5. Our findings are consistent with a recent scRNA-seq study on mouse implantation sites at E5.5, which identified Il33 transcripts in Hoxa11 -positive decidual stromal cells arising during the “second wave” of decidualization that follows blastocyst implantation ( 51 ).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Regardless of the role ethnicity plays, since sST2 levels were not significantly influenced by age and BMI, our differences may have been caused by the range of gestational ages during blood collection. Our study had a slightly wider gestational age range compared to the previous study (30–38 and 30–34 weeks of gestation, respectively), which could contribute to these differences [10] , [15] , [16] , [17] . Concentrations of sST2 were relatively constant until 30 weeks of gestation, after which they increased steadily until the time of delivery due to changes in cytokine concentrations and in the volume of maternal circulation, both of which increased endothelial cell production of sST2 [11] .…”
Section: Discussionmentioning
confidence: 66%
“…We also found upregulation of several immune‐related genes, such as interleukin 33 ( IL33 ), interleukin receptors ( IL4R , IL21R , IL10RA ), interleukin 1 receptor like 1 ( IL2RL1 ), monocytes‐derived plasminogen activator inhibitor 2 ( SERPINB2 ), eosinophil‐attracting chemokine ( CCL11 ), C‐C motif chemokine receptor 1 ( CCR1 ), syndecan binding protein 2 ( SDCBP2 ), which is a chemokine coreceptor, and the proinflammatory cytokine lipocaline 2 ( LCN2 ). IL33 expression is upregulated following proinflammatory stimulation (Begum et al, 2020), IL4 is produced by activated T‐cells and has a role in regulating porcine CL acting via ILR4 (Sakumoto et al, 2006), while IL21 inhibits angiogenesis acting via ILR21 in endothelial cells (Castermans et al, 2008). Moreover, eosinophils accumulate within the CL before regression, and were shown to be the most prominent blood cell type in the porcine regressing CL (Standaert et al, 1991).…”
Section: Discussionmentioning
confidence: 99%